EFEKTIVITAS METODE CERAMAH BERVARIASI DALAM PEMBELAJARAN SEJARAH GUNA MENINGKATKAN HASIL BELAJAR SISWA - Lestari, Tia; Nanda, Shelia; Syariffudin (Fakultas Keguruan dan Ilmu Pendidikan Universitas Kristen Satya Wacana, 2024)
In learning activities, there are many methods that teachers can use in teaching, one of which is the varied lecture method. However, this varied lecture method is often considered boring by students. History teachers are one of the teachers who often use the lecture method, whether it's varied lectures or regular lectures. This is one of the reasons students think history is boring. When students feel bored while studying, the learning outcomes obtained by students will decrease. In this case the author aims to see whether varied lecture methods are still effective for use in learning so that they can improve student learning outcomes. The method in this research is a quantitative method using an approach in the form of direct observation. The population of this study was Class 11 of SMA Negeri 1 Sungai Pinang with the sample taken being Class 11 IPS2, totaling 20 people. The research results obtained were that student learning outcomes increased by 36.5% with pre-test results of 31.5% and post-test results of 68%. This means that varied lecture methods are still effective for use in the learning process because they are able to improve student learning outcomes.